Developing Discovery Learning Assisted Peer Tutors To Improve Problem Solving - Zulaiha Zulaiha; Haninda Bharata; Syarifuddin Dahlan (International Journal of Trends in Mathematics Education Research, 2020)
This research is a research development that aims to find out the development of peer learning assisted by peer tutors that can improve students' mathematical problem solving abilities that are valid, practical and effective. This research procedure uses the development of research by Borg Gall. This development stage starts from the preliminary study, the preparation of learning development, validation, initial field trials, and field trials. The subjects of the study were Grade VII students of Al-Huda Jatiagung South Lampung Middle School in the odd semester of the 2019/2020 academic year. Data collection through observation, interviews, questionnaires, and tests of mathematical problem solving abilities. The results showed that the syntax or stages of discovery learning assisted by peer tutors on the set material met valid and practical criteria. Furthermore, the average N-Gain score of students' mathematical problem-solving abilities after using peer tutored assisted discovery learning is more than the average N-Gain score of mathematical problem-solving abilities of students who take conventional learning. It was concluded that the ability to solve mathematical problem solving with peer tutor-assisted discovery learning was more effective than conventional mathematical problem solving skills with conventional learning.